2016
DOI: 10.1007/s11205-016-1302-9
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Change in Youths’ Political Interest

Abstract: Amnå, Ekström, Kerr & Stattin, 2009). Responsible for the planning, implementation, and financing of the collection of data were professors Erik Amnå, Mats Ekström, Margaret Kerr and Håkan Stattin. The data collection was supported by grants from Riksbankens Jubileumsfond. The study has been approved by the regional Ethical Committee at Uppsala, Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 34 publications
2
48
0
1
Order By: Relevance
“…In relation to age differences, we found that political interest and competence had higher stability at age 16 than at age 13. These differences are in line with previous reports on the stability of political interest over time (e.g., Prior, 2010;Russo & Stattin, 2016) and with studies showing that the stability of political attitudes increases with age (e.g., Alwin & Krosnick, 1991). Importantly, no other effects differed between age cohorts: This indicates that -already by the age of 13 -political interest plays a key role in promoting youth's political development.…”
Section: Political Interest and Sociopolitical Development 19supporting
confidence: 91%
“…In relation to age differences, we found that political interest and competence had higher stability at age 16 than at age 13. These differences are in line with previous reports on the stability of political interest over time (e.g., Prior, 2010;Russo & Stattin, 2016) and with studies showing that the stability of political attitudes increases with age (e.g., Alwin & Krosnick, 1991). Importantly, no other effects differed between age cohorts: This indicates that -already by the age of 13 -political interest plays a key role in promoting youth's political development.…”
Section: Political Interest and Sociopolitical Development 19supporting
confidence: 91%
“…People in excellent and good health do show more interest in politics, but the difference compared with those in poor health is not big. This is relevant, as interest is often considered an indicator of motivation and, as such, a major precursor to political participa tion (Russo and Stattin, 2016). We also know from previous research and the results presented in Chapter 3 of this book that there are participation differences between people with differing health statuses.…”
Section: Interest Efficacy and Satisfaction With Democracymentioning
confidence: 95%
“…Longitudinal research has documented age‐related increases in political efficacy, knowledge, and behaviors across this period (e.g., Eckstein, Noack, & Gniewosz, ; Zaff et al., ). Even among stable constructs such as political interest, more malleability is observed in adolescence, and developmental change in political interest occurs in upward and downward directions (Russo & Stattin, ). Indeed, one trajectory does not fit all youth: Whereas some young people show age‐related increases in political engagement over time, others show downward political trajectories or consistent disengagement (e.g., Wray‐Lake, Rote, Victorino, & Benavides, ).…”
mentioning
confidence: 99%